Seismic base isolation by use of a telescoping stepping mechanism. - Martinez-Rodrigo, Maria D.
A new base isolation mechanism corresponding to a variance of the stepping A shaped frame is proposed and its seismic performance is investigated numerically for strong ground accelerations with peak values in the range from 0.5 to 1 g. In its simplest two dimensional form, the system consists of a frame with two telescoping legs pinned at the apex at a sharp angle. The legs are attached to the foundation through a spring and a damper acting in parallel. Both the springs and viscous dampers have bilinear characteristics that make them very stiff in compression but very soft in tension. As the structure rocks sideways, the length of the loaded leg remains essentially constant while the length of the unloaded leg increases. When the ground acceleration changes direction, the process is reversed. The resulting system has three main characteristics : (i) as the structure steps on a rigid leg, the maximum acceleration that can be transmitted to the superstructure is limited to a value which is approximately independent of the amplitude of the ground motionl (ii) there is a systematic lifting of the superstructure with kinetic energy being systematically transformed into potential energy during the strong phase of the ground motion; and (iii) the system is slowly self centering at the end of the earthquake. The seismic performance of the system is evaluated for a tall bridge pier and for a smaller frame that could be used in a multi-story building. The results obtained for the 1940 El Centro ground motion scaled to 1g and for the near field Rinaldi ground motion recorded during the Northridge earthquake show that substantial reductions of the absolute acceleration can be obtained with reasonable relative displacements of the superstructure and small strokes in the isolation devices.
Keywords: Stepping bridge; Seismic isolation; Base isolation; Bridge dynamics